1970
DOI: 10.1177/004051757004000405
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Structure of Cotton Fibers as Revealed by Enzymatic Degradation

Abstract: The morphological appearance of cotton fibers scoured at 100 and 140°C then subjected to a treatment with cellulase, has been examined as a function of the enzymatic action time. The rate of enzymatic digestion varies according to the region of the secondary wall under consideration, and examina tion of the degraded fibers by optical and scanning electron microscopy clearly shows the bilateral structure of cotton. Four zones can be distinguished in the secondary wall, which differ in their accessibility to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…However, it would be premature to draw any definite conclusion at present as to the cause of the bilateral differentiation of the scales. There has been considerable discussion [8,11,17] ] as to whether the apparent &dquo;scale-edges&dquo; on a wool fiber really mark the boundaries of individual cuticular cells or are merely ridges or shoulders moulded on the cuticle, while it is in the follicle, by the serrated internal surface of the inner. root sheath.…”
Section: Visibility Of Changes Produced By Permangaanddquo;atelsait Trementioning
confidence: 99%
See 1 more Smart Citation
“…However, it would be premature to draw any definite conclusion at present as to the cause of the bilateral differentiation of the scales. There has been considerable discussion [8,11,17] ] as to whether the apparent &dquo;scale-edges&dquo; on a wool fiber really mark the boundaries of individual cuticular cells or are merely ridges or shoulders moulded on the cuticle, while it is in the follicle, by the serrated internal surface of the inner. root sheath.…”
Section: Visibility Of Changes Produced By Permangaanddquo;atelsait Trementioning
confidence: 99%
“…Bilateral Differentiation in the Scales of Untreated Fibers . Kassenbeck [17], using electron microscopy, reported that the cuticle was thicker on the para-cortex side of bilateral wool fibers. He considered this to be an inherent feature, but his fibers had been hydrolyzed prior to embedding for sectioning, and it is possible that the differentiation developed during the hydrolysis.…”
Section: Visibility Of Changes Produced By Permangaanddquo;atelsait Trementioning
confidence: 99%
“…leading to larger swelling (Carra et al 1962). This untwisting is supposed to be the reaction to the twisting (Warwicker et al 1966) which arises from the removal of the liquid contained in the lumen, known as the dehydration or desiccation mechanism that occurs at the end of the growth (Hsieh 1999;Kassenbeck 1970;Warwicker et al 1966). As quoted by Hsieh (1999), the twist frequency in the dried cotton hairs (3.9 to 6.5 per mm) is higher than the S-Z reversals in the cellulose layers (1 to 3 times per mm).…”
Section: Introductionmentioning
confidence: 99%
“…two groups according to accessibility,,, the least accessible group AB, with zone A even less accessible than zone B, and the more accessible group CN, with zone & d q u o ; N even more accessible than zone C. I~Cassenbeck postulated that the differences between these two groups was considerably greater than within each group, hence the concept of the bilateral structure of the cotton fiber. Further evidence for these differences in the cotton structure, which appear during swelling with methacrylate, was revealed by enzymatic degradation [6] of the fiber cross section as well as differential uptake of electron dense staining materials [7]. In every case, this bilateral phenomenon has been attributed to the development of differential stresses during the collapse of the cotton fiber on initial drying, which create variation in packing density.…”
Section: Introduction ;mentioning
confidence: 99%